EFEKTIVITAS TEKNIK CONTACTING DALAM MENJANGKAU CALON NASABAH PADA PT - Novitasari, Anargya Tia; Aminah, Siti (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Contacting is an initial communication technique used to establish relationships with potential customers in marketing activities, especially in brokerage companies. This study aims to analyze the effectiveness of the contacting technique in reaching potential customers at PT Victory International Futures during internships. The contacting process is carried out primarily through familiar individual message-based communication, and is assisted by telephone communication in certain situations. Contacting aims to introduce the company and offer services through a personal approach that is not hard selling. The results of the activity show that contacting via text messages is more effective than by telephone, as it provides a more comfortable, structured communication space that does not interfere with the prospective customer's time. In addition, the internship provides an understanding of the appropriate communication patterns, follow-up techniques, and strategies for building initial interest among prospective customers, even though the final decision remains at their discretion. ABSTRAK Contacting merupakan teknik komunikasi awal yang digunakan untuk menjalin hubungan dengan calon nasabah dalam kegiatan pemasaran terutama dalam perusahaan pialang. Penelitian ini bertujuan untuk menganalisis efektivitas teknik contacting dalam menjangkau calon nasabah pada PT Victory International Futures selama kegiatan magang. Proses contacting dilakukan terutama melalui komunikasi berbasis pesan individu yang sudah dikenal, serta dibantu dengan komunikasi telepon dalam situasi tertentu. Contacting bertujuan untuk memperkenalkan perusahaan dan menawarkan layanan melalui pendekatan personal yang tidak bersifat hard selling. Hasil kegiatan menunjukkan bahwa contacting melalui pesan teks lebih efektif dibandingkan secara telepon, karena memberikan ruang komunikasi yang lebih nyaman, terstruktur, dan tidak mengganggu waktu calon nasabah. Selain itu, kegiatan magang memberikan pemahaman mengenai pola komunikasi yang tepat, teknik follow-up, dan strategi membangun ketertarikan awal calon nasabah meskipun keputusan akhir tetap berada pada pertimbangan mereka.